2014
DOI: 10.1016/j.infbeh.2014.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of parental responsiveness intervention for toddlers at high risk for autism

Abstract: This study tested the effects of a parent-mediated intervention on parental responsiveness with their toddlers at high risk for an autism spectrum disorder (ASD).Participants included caregivers and their 66 toddlers at high risk for ASD. Caregivers were randomized to 12 sessions of an individualized parent education intervention aimed at improving parental responsiveness or to a monitoring control group involving 4 sessions of behavioral support. Parental responsiveness and child outcomes were measured at thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(151 citation statements)
references
References 22 publications
4
143
1
Order By: Relevance
“…Due to the significant role of joint engagement in children’s development, it is critical to target joint engagement for children with ASD in order to maximize their opportunities to learn from interactions with parents. Evidence of improvement in child-initiated joint engagement for children with ASD is found in a number of recent randomized controlled trials of parent-mediated interventions (Kasari et al 2010, 2014a, b, 2015). While time jointly engaged is positively associated with parental responsive behaviour at baseline of intervention (Patterson et al 2014), parental responsiveness has not been examined in relation to changes in joint engagement over the course of a parent-mediated intervention.…”
Section: Longitudinal Associations: Responsivity and Child Outcomes Imentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the significant role of joint engagement in children’s development, it is critical to target joint engagement for children with ASD in order to maximize their opportunities to learn from interactions with parents. Evidence of improvement in child-initiated joint engagement for children with ASD is found in a number of recent randomized controlled trials of parent-mediated interventions (Kasari et al 2010, 2014a, b, 2015). While time jointly engaged is positively associated with parental responsive behaviour at baseline of intervention (Patterson et al 2014), parental responsiveness has not been examined in relation to changes in joint engagement over the course of a parent-mediated intervention.…”
Section: Longitudinal Associations: Responsivity and Child Outcomes Imentioning
confidence: 99%
“…Pickles et al (2015) report partial mediation of the effect of the Preschool Autism Communication Trial (PACT) treatment on autism symptoms by both parent synchrony and child initiations. However, intervention studies of the Focused Playtime Intervention targeting parental synchrony (Siller et al 2013; Kasari et al 2014a, b) have focused on improved outcome in children’s communication skills. In the case of these two studies, both documented increases in parental responsivity post treatment, however, Kasari et al (2014a, b) found no related gains in children’s communication outcomes and Siller et al (2013) found only small gains for children with the greatest language delays.…”
Section: Parent-mediated Interventions: Influence On Parents’ Responsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions aimed at fostering early socialemotional development in ASD may need to focus first on increasing child orienting to a social partner and parent responsiveness [4,48]. Some existing parent-or teacher-mediated approaches with toddlers have yielded gains related to social orienting or engagement [49][50][51].…”
Section: Social-emotional Developmentmentioning
confidence: 99%
“…We identified 2 additonal studies of EIBI (118,119), one of TEACCH (120), four of social skills training (121)(122)(123)(124), and five of interventions involving significant others related to the parent-mediated treatment of children with ASD (excluding EIBI) (125)(126)(127)(128)(129). All studies reported findings that were in favor of the respective intervention method evaluated, with small to large effect sizes; however, study samples were mostly small to medium large (i.e., N = 11 to N = 86).…”
Section: Crude Search Update On Randomized Controlled Studies Of All mentioning
confidence: 99%